Eksistensi Usaha Kuliner Tradisional Bali Dalam Meningkatkan Perekonomian Di Kota Denpasar: Eksistensi Usaha Kuliner Tradisional Bali Dalam Meningkatkan Perekonomian Di Kota Denpasar - Putu Ari Mulyani Ari Mulyani; Nih Luh Indiani (TALI JAGAD JOURNAL, 2024)
The emergence of new trends in the culinary world has slightly displaced traditional culinary businesses. This is due to the influx of food business products from abroad, which are widely distributed in the city of Denpasar and tend to be popular among the millennial generation. The entry of various foreign food products forces traditional culinary establishments to maintain their existence. Therefore, government policies aimed at promoting traditional culinary businesses are expected to continue optimizing the community's efforts to increase the use of local products, enabling traditional culinary businesses to compete. The study used the accidental sampling method with a total of 100 respondents. The tests employed included validity tests, reliability tests, normality tests, heteroscedasticity tests, multicollinearity tests, multiple linear regression tests, F-tests, t-tests, and the coefficient of determination test. The study concluded that lifestyle, food quality, and product availability partially have a positive and significant impact on the existence of traditional culinary businesses in Bali